The role of investment in the cognitive ability production function : evidence from Colombia, Chile, and Peru (2017)
We analyze the role of parental investments on time and parental investments on goods and services on the accumulation of children¿s cognitive skills in Colombia, Chile and Peru. Unlike various related studies, we control for endogeneity biases using a quasi-structural methodology. We can correct for measurement error in investments and endogeneity caused by unobserved child characteristics. We find that parental time investments are more effective in increasing cognitive abilities than investments on goods and services. Additionally, educated mothers invest more on their children. Finally, we confirm the self-productivity evidence foundin related studies.